Hybrid Approach Optic Disc Segmentation for Retinal Images - Tuncer, Seda Arslan; Selcuk, Turab; Parlak, Merve; Alkan, Ahmet (Ieee, 2017)
Detection of optic disc in retinal images is an important step in disease diagnosis and patient follow-up. Optic disc detection is a Preprocess step for the diagnosis of many diseases, such as glaucoma and DP (Diabetic Retinopathy), which are vital for the eye. In this study, a hybrid approach is proposed for fully automatic segmentation of Optic Disc (OD). The first phase of the study consists of OD localization. The OD localization coordinate obtained in the study was used as an input to the method of region segmentation, which is a semi-automatic segmentation method, used as an initial point for OD segmentation. In this way, fully automatic segmentation is done. The success of the hybrid approach was evaluated according to both localization and segmentation. Performance of the study was evaluated with 30 images according to Dice and Jaccard Similarity. As a result of the evaluation have been obtained respectively % 92 and % 87 success.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Optick disk Segmentation; l(1) minimization; Region growing